(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There are 800 main castes and 5000 sub-castes in India. Caste system has existed in India for 3000 years. In the caste system consisting of four categories namely Brahmin, Regional, Vaishya, Shudra, Brahmin is considered sacred in Hindu Dharma Shastra. Carpenters, chambhars, barbers, potters, washermen, goldsmiths are called Balutedars. Indian history mentions many nomadic and freed castes. Ghisadi, Dombari, Kaikadi, Vanjari, Dhangar, many similar tribes living a nomadic life are widely found in India